2006
DOI: 10.1103/physrevlett.97.237202
|View full text |Cite
|
Sign up to set email alerts
|

Clustering in a Precipitate-Free GeMn Magnetic Semiconductor

Abstract: We present the first study relating structural parameters of precipitate-free Ge 0:95 Mn 0:05 films to magnetization data. Nanometer-sized clusters -areas with increased Mn content on substitutional lattice sites compared to the host matrix -are detected in transmission electron microscopy analysis. The films show no overall spontaneous magnetization at all down to 2 K. The TEM and magnetization results are interpreted in terms of an assembly of superparamagnetic moments developing in the dense distribution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
153
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 18 publications
15
153
0
Order By: Relevance
“…For temperatures below 18 K, the precipitate-free T S = 60 • C sample exhibits magnetic signatures of a transition into a metastable state, which we proposed 16 to be a consequence of the formation of coherent clusters. These magnetic signatures are observed for samples with T S > 60 • C in the same temperature range.…”
Section: Metastable Regimementioning
confidence: 99%
See 1 more Smart Citation
“…For temperatures below 18 K, the precipitate-free T S = 60 • C sample exhibits magnetic signatures of a transition into a metastable state, which we proposed 16 to be a consequence of the formation of coherent clusters. These magnetic signatures are observed for samples with T S > 60 • C in the same temperature range.…”
Section: Metastable Regimementioning
confidence: 99%
“…A thorough analysis of the precipitatefree T S = 60 • C sample reveals that this behaviour can be interpreted as a magnetic signature of the coherent clusters. 16 The real part of the AC susceptibility of the T S = 85 • C sample presented in Fig. 4 shows two well separated peaks, one at low temperatures, and one which coincides with the characteristic temperature T B .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…It has been observed that the ferromagnetism with high transition temperatures originates from the formation of nano-scale regions containing magnetic elements in high contents [2][3][4]. In our previous publication, we reported that the ferromagnetic properties of Zn 1-…”
Section: Introductionmentioning
confidence: 99%
“…At T S = 60°C, thin films consist solely of selfassembled Mn-rich Ge 1−x Mn x nanoclusters embedded in a Ge matrix with diamond-type lattice. 4 Increasing the fabrication temperature beyond 60°C additionally leads to the precipitation of nanometer-sized inclusions of the intermetallic compound Mn 5 Ge 3 in the Ge matrix. 8 This is shown in trast corresponding to self-assembled Ge 1−x Mn x nanoclusters.…”
mentioning
confidence: 99%
“…1-3 The latter was observed in epitaxially fabricated GeMn thin films, where specific epitaxy conditions far from thermodynamic equilibrium lead to an inhomogeneous distribution of Mn in the Ge host in the form of self-assembled, nanometer-sized, Mn-rich regions coherently embedded in the Ge-rich host matrix. 1,4 In addition to such thermodynamically metastable Ge 1−x Mn x nanoclusters, a small number of Mn x Ge y intermetallic compounds are known, like, for example, Mn 5 Ge 3 . Mn 5 Ge 3 is a magnetically hard compound 5 with a Curie temperature near room temperature 6 and a hexagonal lattice structure.…”
mentioning
confidence: 99%